Amenders and Avoiders: an examination of guilt and shame for toddlers and their older siblings. Issue 5 (4th July 2022) - Kolak, Amy M.; Volling, Brenda L.
ABSTRACT: Guilt- and shame-prone responding were examined in a sample of 146, 18-month-old toddlers and their older siblings ( M  = 49.5 months, SD  = 10.4) during mishap tasks which were used to differentiate both toddlers and their older siblings into Amenders (low avoidance) and Avoiders (high avoidance). Toddlers and older siblings classified as Amenders expressed more concern and were less distressed by the mishap than Avoiders. Children were divided into four groups: Amender-Amender (older sibling-toddler), Amender-Avoider, Avoider-Avoider, and Avoider-Amender to examine differences in sibling interaction and moral development. Older siblings in the Avoider-Avoider group were significantly more aggressive and less empathic toward toddlers than older siblings in the Avoider-Amender group. Toddlers in the Amender-Amender, Amender-Avoider, and Avoider-Amender groups showed significant gains in moral regulation from 18 to 24 months whereas toddlers in the Avoider-Avoider group did not. In contrast, while older siblings were generally high on moral regulation when toddlers were 18 months, this was not the case for older siblings in the Avoider-Avoider group, who had lower moral regulation scores that significantly increased over time. Findings are discussed with respect to the significance of sibling socialisation for toddlers' developing moral sensibility.